A monument to a scientific pogrom - V. G. Bass (Шаги)
A review of: Molok, N. (2023). David Arkin: “Ideolog kosmopolitizma” v arkhitekture [David Arkin: “An ideologist of cosmopolitanism” in architecture]. Novoe literaturnoe obozrenie. (In Russian).